2015
DOI: 10.1371/journal.pone.0118365
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Treatment, and Control of Diabetes in Bangladesh: A Nationwide Population-Based Study

Abstract: ObjectivesTo examine awareness, treatment, and control of diabetes mellitus among the adult population in Bangladesh.MethodsThe study used data from the 2011 nationally representative Bangladesh Demographic and Health Survey (BDHS). The BDHS sample is comprised of 7,786 adults aged 35 years or older. The primary outcome variables were fasting blood glucose, diagnosis, treatment, and control of diabetes. Multilevel logistic regression models were used to identify the risk factors for diabetes awareness.ResultsO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
77
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 40 publications
15
77
4
Order By: Relevance
“…The BDHS 2011 showed the overall, agestandardized prevalence of diabetes and pre-diabetes to be 9.7% and 22.4%, respectively; among urban residents, the age-adjusted prevalence of diabetes was 15.2% compared with 8.3% in rural residents. 67,68 The prevalence of diabetes mellitus was 7.4% (95% CI 7.2-7.7%) in a recently published review involving 51,252 participants, and also there was an increasing trend of diabetes prevalence among urban and rural population in Bangladesh. 69 According to the International Diabetes Federation assumption in 2010, the explosion in diabetes prevalence will place Bangladesh among the top 7 countries in terms of the number of people living with diabetes in 2030.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…The BDHS 2011 showed the overall, agestandardized prevalence of diabetes and pre-diabetes to be 9.7% and 22.4%, respectively; among urban residents, the age-adjusted prevalence of diabetes was 15.2% compared with 8.3% in rural residents. 67,68 The prevalence of diabetes mellitus was 7.4% (95% CI 7.2-7.7%) in a recently published review involving 51,252 participants, and also there was an increasing trend of diabetes prevalence among urban and rural population in Bangladesh. 69 According to the International Diabetes Federation assumption in 2010, the explosion in diabetes prevalence will place Bangladesh among the top 7 countries in terms of the number of people living with diabetes in 2030.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…[23][24][25] The rates of diabetes awareness (50%), glycaemic control (<30%), and chronic kidney disease awareness (<15%) are suboptimal. [24][25][26][27][28] Delay or prevention of diabetes in South Asians will require earlier intervention-that is, at lower levels of glycaemia. This requires wider testing and earlier use of antihyperglycaemic treatment, complemented with population-wide strategies to drive change in dietary habits and physical activity.…”
Section: Effects Of Poor and Inconsistent Treatmentmentioning
confidence: 99%
“…[15][16][17][18][19] Our study demonstrated that 94.2% of study subjects were non-diabetic, 5.4% of study subjects were pre-diabetic and 0.4% of study subjects were diabetic (Figure 1). Sayeed et al 1995 conducted a study in rural Bangladesh and found the prevalence of type 2 diabetes was 2.1% (male 3.1% and female 1.3%).…”
Section: Discussionmentioning
confidence: 71%